Clingo2DSR - A clingo-based software system for declarative spatial reasoning - Li, Beidi; Schultz, Carl (Spatial cognition and computation, 2025)
We present a modified ground-and-solve approach based on the clingo Answer Set Programming (ASP) system to perform non-monotonic spatial reasoning tasks, Clingo2DSR. Our system is distinct from previous research integrating ASP with space in that it deals with complex real-world data and numerous time steps. Clingo2DSR is composed of (i) an input language defining spatial entities, functions, and relations; (ii) an external geometry database for performing spatial computations and checking spatial constraints; and (iii) a theory-based solving approach coupling symbolic ASP with external sources for sound and fast model search. We demonstrate our system on three real building models, in the context of architectural design, submitted for analyses and queries where spatial components play an important role.